The Difference of High Sensitivity-C Reactive Protein in the Diabetic Patient with depression and Diabetic Patiens without Depression - A. Siswanto, E. Mudjaddid Hamzah Shatri, Deddy N.W.Achadiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Both depression and diabetes mellitus have been related to a higher risk of developing coronary heart disease. Inflammation may be important in the pathogenesis of atherothrombosis. There are many markers of inflammation, one of them is high sensitivity-C reactive protein. Objective: To determine the difference of high sensitivity-C reactive protein in the diabetic patients with depression and in the diabetic patients without depression. Methods: This study used cross-sectional design and examined 64 diabetic patients, aged 30-60 years old. The patients were divided into two groups, Le. with and without depression group.We measured depression using the DSM IV. The diagnosis of diabetes mellitus used PERKENI criteria 2006. We measured the serum concentration of CRP with a high sensitivity assay. Other measured factors included gender, marital status, occupation, blood glucose, HbA 1 c, body mass index, smoking and duration of diabetes. The association between hyperglycemia and hs-CRP were also studied. Results: There were 32 diabetic patients with depression and 32 diabetic patients without depression. Body mass index were corelated with depression in diabetic patients (p = 0.008) but the other factors such as gender, age, marital status, occupation, blood glucose, HbA 1 c, duration of diabetes were not corellated with depression in diabetic patients (p > 0.05). The mean of hs-CRP consentration was higher in diabetic patients with depression (5183.44:t3974.66 vs 2103,17:t1502.94 mg II, p=0.001) than in diabetic patients without depression. There was no association between blood glucose control (HbA 1 c) and hs-CRP concentration. Conclusion: High sensitivity-C reactive protein concentration was higher in diabetic patiens with depression compared with diabetic patients without depression.Key words: hs-CRP - with and without depression diabetes mellitus type II